EVALUASI KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) DI TINGKAT SEKOLAH MENENGAH PERTAMA NEGERI (SMPN) DI KABUPATEN PAMEKASAN - Hasbullah ,; Syaiful Anam (REFORMASI, 2019)
This study focused on evaluating the implementation of the Zoning System policy, this is due to the response of the people in the research locations, namely in SMP 3 Pademawu Subdistrict, Pamekasan Regency, there are some who support and some complain and ultimately surrender to the policies that have government. The researcher used William Dunn's theory as a scalpel in analyzing the zonation system policy in receiving this student boarding ceremony. This study uses qualitative research. The location of the study was at the State Junior High School 3 Junior High School in Pademawu Subdistrict, Pamekasan Regency. The research subjects used purposive sampling. The researcher acts as an instrument that goes directly to the location of the study by using data collection techniques in the form of unattended interview techniques, guided free interviews (documentation interviews) and documentation techniques. The data analysis technique uses an interactive analysis model from Miles and Huberman which has three components, namely Data Collection, Data Condensation, Data Display and Conclusion Drawing / Verification. The results of this study are expected to contribute to the government in making and implementing policies specifically related to the implementation of the zoning system in the acceptance of new students in the future.